The Position Of Legal Philosophy From The Viewpoint Of Islamic Legal Science - Wahida Ariyanti Nasution; Adinda Putri Hutabarat (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
Legal philosophy is an important part of the legal scientific framework, serving to answer fundamental questions about the nature of law, its purpose, and its underlying values. From an Islamic perspective, legal philosophy holds a strategic position as a tool for understanding the sharia values that underlie God's laws. This study aims to outline the position of legal philosophy within the perspective of Islamic legal science. A qualitative approach using a literature review method was used in this paper. The results of the study indicate that Islamic legal philosophy occupies a fundamental position as a foundation for formulating and interpreting law, as well as a link between divine revelation and human rationality. Thus, Islamic legal philosophy addresses not only legality but also the morality and spirituality of law